High deadline meeting rate of non-preemptive dynamic soft real time scheduling algorithm - Zahereel Ishwar, Abdul Khalib, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Proceeding of The International Conference on Control System, Computing and Engineering 2012 (ICCSCE 2012) at Penang, Malaysia on 23 November 2012 through 25 November 2012